Correspondence of Wacław Hieronim Sierakowski in the Dresden Archives Collection. Edition of Letters Bishop of Kamieniec and Przemyśl From the Years 1742–1759 - Perłakowski, Adam (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
Wacław Hieronim Sierakowski was, without a doubt, one of the most distinctive figures of the Saxon period and the beginning of Stanisław August Poniatowski’s times. While he was not part of the innermost circle of politicians who held the fate of the state in their hands, he was more focused on his ecclesiastical career, but he was also quite savvy about politics. He was able to assess the Commonwealth’s international position and to diagnose the greatest threats to its existence. Moving up the church hierarchy, as the Bishop of Kamieniec, Bishop of Przemyśl and finally Archbishop of Lviv, Sierakowski played the leading role in governing his dioceses, standardising their structure, developing education, expanding the network of parishes and acting as patron of many artistic and building projects. The letters edited in the present text show Sierakowski as a faithful supporter of the court, who cared about his family, for instance as regards vacant positions in offices. At the same time they define him as a typical man of the eighteenth century, who did not propose great reforms or bold plans and who adopted a stance, which was shared by many representatives of the power elites similar to him.